2020
DOI: 10.1108/rjta-10-2019-0049
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behaviour of heat treated polyester knitted fabrics

Abstract: Purpose Thermoplastic polymer fabrics are normally heat set to make them dimensionally stable. These fabrics in garment panel form may again be exposed to heat during the processes such as bonding, sublimation printing and cause to change their dimensions. The purpose of this paper is to investigate the response of polyester yarns in knitted fabrics to heat setting and post-heat treatments. Design/methodology/approach In this study, the thermal shrinkage behaviour of heat set polyester knitted fabrics when s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In addition, below the Ts, mechanical deformations may occur. In polyester PET, with a Ts of 238 °C, mechanical deformations begin to occur from 140 °C [ 44 ], in cotton at 200 °C, in ramie at 250 °C, and in wool at 150 °C [ 45 ]. Above these temperatures, the shape and size of the fiber will change and shrink, and it will not return to its original state after cooling, which is called fiber thermal shrinkage.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, below the Ts, mechanical deformations may occur. In polyester PET, with a Ts of 238 °C, mechanical deformations begin to occur from 140 °C [ 44 ], in cotton at 200 °C, in ramie at 250 °C, and in wool at 150 °C [ 45 ]. Above these temperatures, the shape and size of the fiber will change and shrink, and it will not return to its original state after cooling, which is called fiber thermal shrinkage.…”
Section: Methodsmentioning
confidence: 99%
“…56 The bonds within the fibers break causing distortion such as shrinkage or expansion. 57 Perera and Lanarolle tested polyester fiber with a glass transition temperature of 89°C at different temperatures to determine the expansion and shrinkage of polyester fabrics due to thermal treatment. 56,58 Even the lowest temperature tested, 130°C, was too high and resulted in fiber deformation.…”
Section: Textile Dryingmentioning
confidence: 99%
“…Finally, the thermal characterization of extract-coated catheters was performed to evaluate their thermal stability. Figures 9(a The first thermal region was attributed to the PET melting temperature (T m ), which has been reported to be from 232 °C-250 °C [71][72][73]. Moreover, it was observed that the T m and heat flux necessary for the PET crystallites to melt increased after extract coating and did not depend on the plasma pretreatment.…”
Section: Thermal Characteristicsmentioning
confidence: 99%